Missionnaires au quotidien à Tahiti : les Picpuciens en Polynésie au XIXe siècle - Toullelan, Pierre-Yves, 1955- (Studies in Christian Mission, 1995)
Missionnaires au quotidien à Tahiti immerses us in the everyday life of Catholic missionaries sent out to the Tahitian islands in the period 1834 to 1914. Using the correspondence of the 167 members of the order of the Congregation of the Sacred Heart of Jesus and Mary, an attempt is made to define the social and geographic origins of the Picpucian people. Priests and friars are followed in their education, from the apostolic school to the first Pacific vicariates. Right from the first days of established contact, we see the management of the day-to-day affairs of these eternal travellers, by turns vicars and planters, schoolmasters and builders. Within the framework of a very hierarchical ecclesiastical structure, we watch the elaboration of a social project that quickly extends beyond the bounds of a narrow theocracy. It is on this societal model that a large part of Polynesia rests today.